AN OVERVIEW OF NUCLEAR MAGNETIC RESONANCE - Philips Nicolas Gunawidjaja (INTEGRAL, 2013)
There are a number of techniques available for investigating the structures of materials. One of the most powerful techniques capable of providing information both about the structure of materials and about the dynamics of process within those materials is Nuclear Magnetic Resonance (NMR) Spectroscopy. The purpose of this paper is to give an overview on some of the most important aspects of the background theory of NMR.Keywords: NMR theory.Ada beberapa jenis teknik untuk meneliti struktur material. Salah satu teknik yang sangat ampuh yang dapat memberikan infomasi mengenai struktur materal sekaligus proses dinamik dalam material tersebut adalah Spektroskopi Nuclear MagneticResonance (NMR). Tujuan ditulisnya tulisan ini adalah untuk memberikan sekilas rangkuman mengenai aspek-aspek penting dalam teori NMR.Kata Kunci: teori NMR.